2021
DOI: 10.1057/s41599-021-00876-w
|View full text |Cite
|
Sign up to set email alerts
|

It matters to be in good hands: the relationship between good governance and pandemic spread inferred from cross-country COVID-19 data

Abstract: This study examines the relationship between good governance and pandemic control using month-wise COVID-19 pandemic data within a time window from April to September 2020. The study argues that countries with better governance are more capable of adopting and implementing appropriate policies and that such governments are considered more trustworthy by their people. Combined, these factors enable such countries to better control a pandemic like COVID-19. Using several measures of good governance and two measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…COVID-19 and future epidemics of new viral agents pose a serious environmental threat to countries' national security and public health (Coccia, 2022e). A pandemic can occur with little warning and a delay in detecting a novel infectious disease (sharing virus samples and developing, producing, distributing, or administering vaccines) could result in significant additional morbidity and mortality (Nabin et al. , 2021).…”
Section: Concluding Observationsmentioning
confidence: 99%
“…COVID-19 and future epidemics of new viral agents pose a serious environmental threat to countries' national security and public health (Coccia, 2022e). A pandemic can occur with little warning and a delay in detecting a novel infectious disease (sharing virus samples and developing, producing, distributing, or administering vaccines) could result in significant additional morbidity and mortality (Nabin et al. , 2021).…”
Section: Concluding Observationsmentioning
confidence: 99%
“…In addition, I substitute the overall governance index with one WGI dimension—“Government Effectiveness“. I follow Nabin et al [ 15 ] to do so as “GOV captures the most generic aspects of quality of governance, whereas the other constituents capture more specific aspects”. Regression results in Table 7 also show strong evidence that the relationship between governance quality and policy stringency is inverse U-shaped.…”
Section: Further Robustness Checksmentioning
confidence: 99%
“…Second, COVID-19-related studies have reported the impact of governance quality on the COVID-19-related disease outcomes rather than government responses. For instance, Nabin et al [ 15 ], Baris and Pelizzo [ 16 ], and Liang et al [ 17 ] found that governance quality deputized only by GOV helps to contain the COVID-19 spread and reduce COVID-19-related mortality. Even though Stojkoski et al [ 18 ] included all six dimensions when explaining the COVID-19 disease outcomes, governance quality was treated as the control rather than the predictor.…”
Section: Introductionmentioning
confidence: 99%
“…Tasnim et al (2020) suggest that leadership across organisations should promote the dissemination of accurate information about the pandemic. A study carried out by Nabin et al (2021) suggests an inverse relationship between good governance and the spread of COVID-19 infections. Que et al (2020) urged that positive and objective information about COVID-19 be widely disseminated to the public.…”
Section: Covid-19mentioning
confidence: 99%